„Dalej wzwyż i dalej w głąb”. Średniowieczny rodowód figury raju w narnijskiej septalogii C. S. Lewisa - Morawiecka, Maria Magdalena (2022)
This paper aims to present the possibility of drawing a deeper connection between the medieval imaginarium andselected tropes in twentieth century fantasy literature, based on a case study analysing the concept of paradise inC. S. Lewis’s young adult book series, The Chronicles of Narnia. In order to do that, the article introduces somekey elements and rules governing medieval geographical concepts and how they tie in with the highly symbolicperspective on the world adopted in that epoch, using examples from cartographic and literary sources. Next, theauthor takes a look at the model of paradise carefully crafted in Lewis’s novels, to later compare it with its medievalcounterpart and demonstrate the analogies between the two, with the goal of providing some clues regardingpossible paths for interpretation.
Keywords: Lewis, C. S.